THE ROLE OF DIGITAL-BASED DRUG MANAGEMENT IN IMPROVING THE EFFECTIVENESS AND EFFICIENCY OF THE REPORTING SYSTEM AND ITS IMPLICATIONS FOR DECISION-MAKING IN THE PHARMACY INSTITUTION OF THE GENERAL SERVICES AGENCY OF NABIRE REGENCY GENERAL HOSPITAL - Kristina Boga; Teguh Nurhadi Suharsono; Ayu Laili Rahmiati; Rullia; Vip. Paramarta; Farida Yuliaty (RADJA PUBLIKA, 2025)
The suboptimal provision of medication services at the Pharmacy Unit of Nabire Regency General Hospital is a problem at the Public Service Agency of Nabire Regency General Hospital. This study aims to analyze the role of digital-based medication management in improving the effectiveness and efficiency of the reporting system and its implications for decision-making at the Pharmacy Unit of Nabire Regency General Hospital. This study used qualitative research methods, including interviews, observation, and documentation. The results of the study indicate that the role of digital-based drug management in improving the effectiveness and efficiency of the reporting system and the implications for decision-making at the Pharmacy Installation of the Public Service Agency of the Nabire Regency General Hospital is still not running well. This is seen in the following: The selection stage is routinely every year to compile drug needs by involving all managers with activities to adjust available drug items but still below the standards of the Indonesian Ministry of Health. The procurement stage by carrying out planning and procurement through the stages of providing available capital/funds with the entire required funds sourced from the Regional Budget and Special Autonomy Funds and the procurement of each drug item as of May 2025 as many as 278 types of drugs. The distribution stage by looking at the match between the drug and the stock card to avoid the condition of drug stock in the empty, insufficient, safe or excess category and to affect the requested drug demand and the level of drug availability for 12 months. The user stage by looking at the number of drug items per prescription sheet that have been listed in the system but there are some drug items that cannot be served and drugs that are correctly labeled have complied with the rules. Suggestions for the need to improve selection so that drug needs are in accordance with the standards of the Indonesian Ministry of Health, adding funds so that all drugs are available, monitoring drug distribution by matching drugs with stock cards and providing drug items for each prescription sheet in full.